PENGEMBANGAN LEMBAR KERJA SISWA (LKS) YANG DIAWALI PETA KONSEP DISERTAI GAMBAR PADA MATERI JARINGAN HEWAN UNTUK SISWA SMA - Wardhani, Martia; nerita, siska; Susanti, Diana (STKIP PGRI Sumbar, 2014)
ABSTRACT Media of teaching is hold the important role in teaching learning process and can improve the quality of learning process. Teacher as facilitator must able in make interest and innovative. The teaching material each of media of teaching in the school is LKS. The using of LKS in learning process at school can give the big opportunity to students for get the best achievementin learning. Based on the observation and interview which have been conducted toward teacher and student that in SMAN 1 sungai limau, the student use the LKS as guided in learning process. The LKS that use by the students, serve the material that too long, and the picture have not colour so the LKS is unclear ans less interest, besides that LKS do not have have concept map. The purpose or this research is to resulted LKS that begin with concept map along with picture in animal network material which valid and practical. The research of LKS that begin with concept map along with picture in animal network material is develop by using model 4-D, consist of step define, design step, develop step and disseminate step, but in this research only in develop step because of limited cost and time. The result of this research, get the average of value in test validity that fill by the lecturer and teacher that is 89,17% with some aspect of validity criteria of didaktik, construction and technique, mean while the praktikalitas test that doing by the teacher is88,27% with very practical criteria and the praktikalitas value by students get 82,89% whit practical criteria. From the result of which obtained in conclusion, LKS have develop, valid and very practical for the teacher and practical for students.